2002
DOI: 10.1007/s00442-002-0915-7
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of pressurized ventilation, water depth and substrate conditions on Phragmites australis

Abstract: Pressurized ventilation acts to increase the oxygen supply to roots and rhizomes in some species of emergent plants. In a greenhouse experiment, we investigated how pressurized ventilation affected growth, biomass allocation and mineral content of Phragmites australis in two water depths (15 cm or 75 cm) and two substrates (organic sediment or sand). Through perforating each stem above the water surface, pressurized ventilation was inhibited without affecting oxygen diffusion. In controls, 10-20% of the stems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 46 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…This is indicated by the work of Vretare & Weisner (2000), who found that in Phragmites , when convective flows are permitted, rhizome growth in terms of length, numbers and biomass is increased. They also showed (Vretare Strand & Weisner, 2002) that for plants growing in organic sediment, convective flows promoted greater O 2 concentrations in stem bases and greater uptake of certain minerals.…”
Section: Discussionmentioning
confidence: 96%
“…This is indicated by the work of Vretare & Weisner (2000), who found that in Phragmites , when convective flows are permitted, rhizome growth in terms of length, numbers and biomass is increased. They also showed (Vretare Strand & Weisner, 2002) that for plants growing in organic sediment, convective flows promoted greater O 2 concentrations in stem bases and greater uptake of certain minerals.…”
Section: Discussionmentioning
confidence: 96%
“…Rozbrojová and Hájek (2008) studied nutrient levelsincluding Fein a mountain fen, and found that poor vegetation growth was correlated with high levels of Fe (above 150 µg/g in vegetation tissue). Of the limited studies published on the relationship between wetland plant growth and Fe or Mg, only a few have focused on their effects on Phragmites australis (Snowden and Wheeler 1993;Weisner 1996, Vretare-Strand and Weisner 2002, Batty and Younger 2003, Gigante et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of this study was to understand how two nutrients necessary for chlorophyll production, iron and magnesium, affected the growth of native Phragmites from rhizomes to a healthy, non-chlorotic, adult stage. Magnesium sulfate (MgSO 4 ) and iron sulfate (FeSO 4 ) were used as supplements based upon anecdotal and published evidence suggesting some success in reducing chlorosis in native Phragmites and other wetland plants (Vretare-Strand and Weisner 2002, Saltonstall and Stevenson 2007, Eller et al 2013. We hypothesized that plants given additional Fe(II) and/or Mg(II) would produce more aboveground and belowground biomass and have little or no evidence of chlorosis or other impairment of photosynthetic performance.…”
Section: Introductionmentioning
confidence: 99%
“…The convective through-flow in these aquatic plants is the result of a gas-pumping system, commonly powered by solar radiation, which improves the internal aeration of submerged plant organs (Grosse, Büchel & Tiebel, 1991; Große, 1996; Ribaudo et al, 2012), and confers beneficial effects on the ecosystem (e.g. increased oxygen transfers to rhizosphere, root growth and nutrient uptake, Strand & Weisner, 2002; Nakamura et al, 2013). Nuphar lutea is a representative of this group.…”
Section: Introductionmentioning
confidence: 99%